The Character of The Students in MTs. Al-Mahalli Bantul Yogyakarta (A Comparative Study on Students Staying in Pesantren and Outside Pesantren) - Riska Anintyawati (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo (previously known as IAIN Ponorogo), 2021)
This research aims to reveal: The comparison of character between students living in pesantren and those living outside pesantren in MTs. Al-Mahalli Bantul, Yogyakarta. This research is a comparative study with the quantitative approach. The population is 276 students of MTs. Al-Mahalli Bantul, Yogyakarta. The research sample was the population. The data on character were collected using questionnaire. The validity testing was conducted by expert judgement and exploratory factor analysis (EFA). The reliability was assessed by Cronbach’s Alpha formula. The data analysis techniques included the descriptive technique, tests of prerequisites analysis, i.e. tests of normality and homogeneity. The hypothesis testing used the independent sample T-test at the significance level of 0,05. The results are as follows. There are several characterdifferences between students living in pesantren and those living outside pesantren, the result of hypothesis testing shows that the null hypothesis (H0) is rejected and the alternative Hypothesis (Ha) is accepted (t-arithmetic> t table (7,823> 1,971). There are differences in the average value at each new character between the two groups of students. The religious character value of the students living in pesantren is 3.388, while those living outside pesantren is 3,139. The honest character value of the students living in pesantren is 3,071, while those living outside pesantren is 2,844. The tolerance character value of the students living in pesantren is 3,277, while those living outside pesantren is 3,116. The discipline character value of the students living in pesantren is 3,050, while those living outside pesantren is 2,766. The independent character value of the students living in pesantren is 2,815, while those living outside pesantren is 2,504. The responsible character value of the students living in pesantren is 2,740, while those living outside pesantren is 2,618. Keywords: character; pesantren